THE IMPLEMENTATION OF COMBINING BLENDED LEARNING AND PROJECT BASED LEARNING IN TEACHING EFL CRITICAL READING TO STUDENTS OF STKIP PGRI JOMBANG - HARTIA NOVIANTI HARTIA; Rukminingsih (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2022)
The distance learning policy during the COVID-19 pandemic created new problems for students. The implementation of education and learning has undergone drastic changes. Learning is no longer using conventional face-to-face meetings, but is starting to be integrated with online learning. This is what causes the reading learning process, especially reading comprehension, is lacking. This research is designed to solve problems in reading class. The subjects in this study were students of STKIP PGRI Jombang, students majoring in English Education in the fifth semester who were taking critical reading courses. The research design uses classroom action research. The instruments used here were interviews, observations, field notes, questionnaires, and tests. The results of the study show Combaining of Blended Learning and Project Based Learning in Teaching EFL Critical Reading to Students can be an alternative teaching strategy that benefits for improving students' achievement, ability, and participation in the teaching and learning process